(untitled) - Hart, Harold (Geneva, Ill., 1995)
Contents: Bonding and isomerism; Alkenes and cycloalkanes, conformational and geometric isomerism; Alkenes and alkynes; Aromatic compounds.
Keywords: Chemistry, organic,Hóa học hữu cơ